Intragastric Endoscopic Assisted Single Incision Surgery for Gastric Leiomyoma of the Esophagogastric Junction - Salvador Morales-Conde; Isaias Alarcón; Carlos Ortiz-Moyano; Antonio Barranco; Francisco J. Padillo; María Socas (Case Reports in Gastrointestinal Medicine)
Single port laparoscopic surgery is becoming an alternative to conventional laparoscopic surgery as a new approach where all the conventional ports are gathered in just one multichannel port through only one incision. Appling this technical development, we have developed a new technique based on an intragastric approach using a single port device assisted by endoscopy (I-EASI: intragastric endoscopic assisted single incision surgery) in order to remove benign gastric lesions and GIST tumors placed in the posterior wall of the stomach or close to the esophagogastric junction or the gastroduodenal junction. We present a patient with a submucosal gastric tumor placed near the esophagogastric junction removed with this new approach.